Experimentally and spectroscopically evidenced mechanistic study of butyl peroxyacid oxidative degradation of benzo[a]pyrene in soil. (1st September 2022) - Choi, Jong-Soo; Lim, Seon-Hwa; Jung, Sang-Rak; Lingamdinne, Lakshmi Prasanna; Koduru, Janardhan Reddy; Kwak, Moo-Young; Yang, Jae-Kyu; Kang, Seon-Hong; Chang, Yoon-Young
Abstract: Benzo[a]pyrene (BaP) is a major indicator of soil contamination and categorized as a highly persistent, carcinogenic, and mutagenic polycyclic aromatic hydrocarbon. An advanced peroxyacid oxidation process was developed to reduce soil pollution caused by BaP originating from creosote spills from railroad sleepers. The pH, organic matter, particle size distribution of soil, and concentrations of BaP and heavy metals (Cd, Cu, Zn, Pb, and As) in the BaP-contaminated soils were estimated. A batch experiment was conducted to determine the effects of organic acid type, soil particle size, stirring speed, and reaction time on the peroxyacid oxidation of BaP in the soil samples. Additionally, the effect of the organic acid concentration on the peroxyacid degradation of BaP was investigated using an oxidizing agent in spiked soil with and without hydrogen peroxide. The results of the oxidation process indicated that BaP and heavy metal residuals were below acceptable Korean standards. A significant difference in the oxidative degradation of BaP was observed between the spiked and natural soil samples. The formation of a peroxyacid intermediate was primarily responsible for the enhanced BaP oxidation. Further, butyric acid could be reused thrice without losing the efficacy (<90%). The systematic peroxyacid oxidative degradation mechanism of BaP was also discussed. A qualitative analysis of the by-products of the BaP reaction was conducted, and their corresponding toxicities were determined for possible field applications. The findings conclude that the developed peroxyacid oxidation method has potential applications in the treatment of BaP-contaminated soils. Graphical abstract: Image 1 Highlights: Butyric acid initiated oxidative degradation of benzo [a]pyrene (BaP) in soil. Butyric acid efficiently removed BaP in soil compared to other organic acids. BaP and heavy metal concentrations were reduced under allowed standards. Peroxyacid intermediate enhanced BaP oxidation. Butyric acid could be re-used up to three times without losing its efficacy (<90%).